2012
DOI: 10.1063/1.3686486
|View full text |Cite
|
Sign up to set email alerts
|

MD simulations of laser-induced ultrashort shock waves in nickel

Abstract: Abstract. The dynamics of ultrashort shock waves induced by femtosecond laser pulses were explored in nickel-glass and free-standing nickel films by molecular dynamics simulations. Ultrafast laser heating causes stress-confinement, which is characterized by formation of a strongly pressurized 100-nm-thick zone just below the surface of the film. For low-intensity laser pulses, only a single elastic shock wave was formed despite pressures several times greater than the experimental Hugoniot elastic limit. Becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…In the GLAD film (α = 60 • ), the stresses are approximately half that of the normally deposited film (α = 0 • ). The formation of film layers, with a high value of compress stress under laser irradiation, was demonstrated earlier in the MD simulations [9].…”
Section: E(si) →supporting
confidence: 60%
See 1 more Smart Citation
“…In the GLAD film (α = 60 • ), the stresses are approximately half that of the normally deposited film (α = 0 • ). The formation of film layers, with a high value of compress stress under laser irradiation, was demonstrated earlier in the MD simulations [9].…”
Section: E(si) →supporting
confidence: 60%
“…The stresses in nickel films, caused by femtosecond laser pulses, were studied using molecular dynamics (MD) simulations in Ref. [9]. It was found that ultrafast heating results in the formation of a 100 nm thick strongly compressed layer below the film surface.…”
Section: Introductionmentioning
confidence: 99%
“…The process of nonlinear evolution of wave is described in papers. 23,[29][30][31][32][33] The description in those papers is based on molecular dynamics (MD) simulations. Below in Section 4 we presents new results concerning comparison the 2T-hydrodynamic simulations † and MD.…”
Section: General Picturementioning
confidence: 99%